Fertilização nitrogenada no capim Mombaça em sistema de integração pecuária-floresta intensificado. - André, Tiago Barbalho (2023)
The objective of experimental trial was to evaluate the effects promoted by full sun environments and natural shading (25%), under the productive components of Panicum maximum cv. Mombasa, grown at different levels of nitrogen (kg ha-1 cycle 1 ), in the northern state of Tocantins, Brazil, part of Amazon-Cerrado ecotone. Evaluated variables: total dry mass (MST), dry mass of leaf blade (MSLF), dry mass of stem sheath (MSCo), dry mass of dead material (MSMM), the leaf stem ratio (L/C), tillering (DPP), mass tiller (MP) end economic considerations, number of total sheets (NFT), number of live leaves (NFV), number of dead leaves (NFM), lifespan of the sheet (DVF), length of the sheath (CB), stem elongation rate (TAlC), Phyllochron (FILO), leaf appearance rate (TApF), leaf elongation rate (TAlF), senescence (TSF), average length of leaf blade (CMLF), leaf area index (IAF) and tiller density (DPP), number of total sheets (NFT), number of live leaves (NFV), number of dead leaves (NFM), lifespan of the sheet (DVF), length of the sheath (CB), stem elongation rate (TAlC), Phyllochron (FILO), leaf appearance rate (TApF), leaf elongation rate (TAlF), senescence (TSF), average length of leaf blade (CMLF), leaf area index (IAF) and tiller density (DPP), leaf blade production rate (TPLF), thatched production rate (TPC), forage biomass production rate (TPBFor), leaf loss rate (TPerdaF) and herbage accumulation rate (TAcFor). The addition of nitrogen promoted growth in the availability of total dry mass, with production beginning with 3,683 kg ha-1 cycle-1 , reaching a maximum of 5,729 kg ha-1 cycle-1 , reducing the 5,324 kg ha-1 cycle-1 in full sun, and the natural environment shading 2,619; 3,165 kg ha-1 ; 1,782 kg ha-1 cycle-1 , respectively. Economic production reduces cost by up to 52% in full sun (5,157 kg ha-1 cycle-1 MST with 33 kg ha-1 cycle-1 N), and 76% in natural shading (2,848 kg ha-1 cycle-1 MST with 9 kg ha-1 cycle-1 N). The shaded environment provided better conditions for length of the sheath and leaf elongation rate, however in full sun the tiller density was higher. In full sun the average TPBFor was 187.93 kg ha-1 day-1 , already on the shaded 173.27 kg ha-1 day-1 , representing a difference of 7.80%. The TPC of 24.348 kg ha-1 day-1 in the shaded, was 17.58% higher than in full sun, who got 20.069 kg ha-1 day-1 . The full sun provided 66.44% in TPerdaF with 36.488 kg ha 1 day-1 , already resulted in the shaded 12.247 kg ha-1 day-1.